2003
DOI: 10.1063/1.1565709
|View full text |Cite
|
Sign up to set email alerts
|

Control of tunnel oxide thickness in Si-nanocrystal array memories obtained by ion implantation and its impact in writing speed and volatility

Abstract: The injection and storage of charge in Si nanocrystals obtained by ion implantation and annealing have been studied for different tunnel oxide thicknesses. The energy of the ions was kept fixed at 15 keV, which is compatible with most ion implanters used in Si technology, and the distance between the Si nanocrystals and the substrate was controlled by using gate oxides with different thicknesses. The processing conditions were adjusted for precipitating all the Si excess and for having Si–SiO2 interfaces free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…6. An injection barrier equal to 1.7 eV can be deduced with a threshold voltage equal to 23 V. This value is significantly lower than the injection barrier of pure SiO 2 (3.1 eV), in accordance with an enhancement of the injection of carriers due to the presence of Si-nc [17,18]. Furthermore, above 25 V, white electroluminescence of the layer has been detected (not shown), whose appearance is correlated to the setting of the Fowler-Nordheim regime.…”
Section: Article In Pressmentioning
confidence: 93%
“…6. An injection barrier equal to 1.7 eV can be deduced with a threshold voltage equal to 23 V. This value is significantly lower than the injection barrier of pure SiO 2 (3.1 eV), in accordance with an enhancement of the injection of carriers due to the presence of Si-nc [17,18]. Furthermore, above 25 V, white electroluminescence of the layer has been detected (not shown), whose appearance is correlated to the setting of the Fowler-Nordheim regime.…”
Section: Article In Pressmentioning
confidence: 93%
“…Si nanocrystals in SiO 2 have been extensively studied for more than a decade for the visible photo-and electroluminescence ͑PL,EL͒ originated from quantum confinement effects, [5][6][7][8][9][10] and for the use of Si nanocrystals as nanosize charge-storing elements in flash memories. 11,12 For materials codoped with Er, it was recently shown that amorphous Si nanoclusters ͑Si-nc͒ are as efficient sensitizers as Si nanocrystals. 13 In such codoped systems ͑with either Si nanocrystals or nanoclusters as sensitizers͒, an increase of more than four orders of magnitude of an Ereffective excitation cross section was observed.…”
Section: Introductionmentioning
confidence: 99%
“…This method, unlike doping, uses the low-energy Si þ implantation to reduce introduced defects. Size, density, and location of the nc-Si dots were demonstrated to correlate with the dose and acceleration of ion as well as the subsequent annealing conditions, however hard it may be to make precise control [57]. Other preparation methods that have been used for forming nc-Si dots rely on crystallization of amorphous silicon [58] or aerosol nc-Si dots from silane pyrolysis [31] and various sputtering techniques [59].…”
Section: Bottom-up Methodologymentioning
confidence: 99%